Class Discussions to Improve Students’ Active Participation in A Christian School During Online Learning - Priskila Anggi Diananugeraheni; Juniriang Zendrato (Sekolah Tinggi Theologia Nazarene Indonesia, 2022)
The research was inspired by the facts found in online class observations of primary studentsof Grade V in Tangerang. Some students did not participate in class discussions actively.Therefore, the objectives of this research were to know whether class discussions improvestudents’ active participation during online learning and to explain the steps of classdiscussions to help students to participate actively in online learning. This is classroomaction research. The data was collected from 23 Grade V students of a Christian school inTangerang from July 12, 2021, until August 18, 2021, during online learning. Theinstruments used were the observation form, lesson plan, affective journal checklist, andreflection. The results were class discussions improved students’ responsibility to participateactively, do the assignments, and participate verbally by answering and questioning in classdiscussions. Another result was there were six steps of class discussions, i.e., dividing thestudents into small groups, explaining the steps of good discussion, giving the topic orproblem to be discussed by each group, facilitating the discussion and guiding the students,listening to groups’ presentation and giving each group feedback, as well as assisting thestudents to conclude. The conclusion was the class discussions that were prepared well byChristian teachers would improve primary students' active participation during onlinelearning.